Comparative ionic flux and gill mucous cell histochemistry: effects of salinity and disease status in Atlantic salmon (Salmo salar L) - Roberts, SD; Powell, MD (2003)
Two experiments were conducted to assess the physiological effects of freshwater exposure and amoebic gill disease (AGD) in marine Atlantic salmon (Salmo salar L.). The first experiment monitored marine salmon during a 3 h freshwater exposure, the standard treatment for AGD in Tasmania. The second experiment described the gill mucous cell histochemistry for freshwater adapted and seawater acclimated fish (AGD affected and unaffected) for possible correlations to ionoregulation. When exposed to freshwater, marine Atlantic salmon experienced a minor ionoregulatory dysfunction represented by a net efflux of Cl- ions at 3 h. AGD affected fish experienced the net efflux of Cl- ions 1 h sooner, and had a significantly greater net efflux of total ammonia. Changes to gill mucous cell populations corresponded to differing salinity and the presence of AGD. In AGD affected fish, these populations significantly differed between lesion and non-lesion associated areas of the gill filament. Our results have shown changes in the ionoregulatory capacity of Atlantic salmon due to freshwater exposure and AGD. Gill mucous cell histochemistry indicates the potential importance of the mucous layer in ionoregulation and disease. In comparison to previous studies on rainbow trout, these results suggest that Atlantic salmon have a greater short-term ionoregulatory capacity. Â© 2002 Elsevier Science Inc. All rights reserved.